SPECIFIC FEATURES OF BORROWED PHRASEOLOGICAL UNITS IN ENGLISH AND RUSSIAN LANGUAGES - Seytimbetova Aykumar Pulatbayevna (Western European Studies, 2025)
This article investigates the phenomenon of borrowed phraseological units (PUs) in the modern usage of English and Russian. Drawing on comparative and contrastive phraseological studies, it explores structural, semantic, and functional features of such borrowings, including their origins, integration processes, and cross-cultural significance. Particular attention is paid to mechanisms of borrowing (calques, literal translation, calqued idioms), adaptation into the recipient language, semantic equivalence versus non-equivalence, and the role of cultural context in acceptability and usage. The study shows that, while many borrowed PUs undergoes full integration and function like native idioms, a substantial portion remains semi-transparent or marked as “foreign,” which affects their acceptability, interpretation, and translation. The article underscores the importance of cultural and linguistic competence in the use and translation of phraseological borrowings, and discusses implications for phraseology, translation studies, and intercultural communication.
Keywords: borrowed phraseological units; idioms; calques; translation